Our cups are full pottery and society in the Aegean Bronze Age : papers presented to Jeremy B. Rutter on the occasion of his 65th birthday - Gauß, Walter 1969-; Lindblom, Michael 1969-; Smith, R. Angus K. 1968-; Wright, James C. 1946- (Archaeopress, 2011)
This is a collection of papers presented to Jeremy Rutter to mark his 65th birthday